Percy And The Pirates - Russell Punter & Kate Sheppard
This title is part of four new titles in the fantastic "First Reading" series, aimed at children who are beginning to read. Luxurious hardback editions foster pride in book ownership and enthusiasm for reading. Each of these four exciting new stories is a classic story or fable, retold with simple text to delight and inspire any child who is just beginning to read. This key series was developed in conjunction with reading expert Allison Kelly from the University of Surrey, a reading specialist. Every title has clear and compelling text that allows children to build their burgeoning reading skills and is accompanied by charming and highly appealing illustrations.